Role of Systematic Biopsy in the Era of Targeted Biopsy: A Review - Wojciech Malewski; Tomasz Milecki; Omar Tayara; Sławomir Poletajew; Piotr Kryst; Andrzej Tokarczyk; Łukasz Nyk (Current Oncology, 2024)
Prostate cancer (PCa) is a major public health issue, as the second most common cancer and the fifth leading cause of cancer-related deaths among men. Many PCa cases are indolent and pose minimal risk, making active surveillance a suitable management approach. However, clinically significant prostate carcinoma (csPCa) can lead to serious health issues, including progression, metastasis, and death. Differentiating between insignificant prostate cancer (inPCa) and csPCa is crucial for determining appropriate treatment. Diagnosis of PCa primarily involves trans-perineal and transrectal systematic biopsies. Systematic transrectal prostate biopsy, which typically collects 10–12 tissue samples, is a standard method, but it can miss csPCa and is associated with some complications. Recent advancements, such as magnetic resonance imaging (MRI)-targeted biopsies, have been suggested to improve risk stratification and reduce overtreatment of inPCa and undertreatment of csPCa, thereby enhancing patient quality of life and treatment outcomes. Guided biopsies are increasingly recommended for their ability to better detect high-risk cancers while reducing identification of low-risk cases. MRI-targeted biopsies, especially when used as an initial biopsy in biopsy-naïve patients and those under active surveillance, have become more common. Utilization of MRI-TB alone can decrease septic complications; however, the combining of targeted biopsies with perilesional sampling is recommended for optimal detection of csPCa. Future advancements in imaging and biopsy techniques, including AI-augmented lesion detection and robotic-assisted sampling, promise to further improve the accuracy and effectiveness of PCa detection.